Outcome of tenonplasty in scleral ischemia secondary to acute ocular surface burn - Nidhi Gupta; Shweta Singh; Virender Sangwan; Umang Mathur (Indian Journal of Ophthalmology)
Purpose: To study the outcome of tenonplasty in eyes with perilimbal ischemia in acute ocular surface burns. Methods: This was a single-center retrospective study that included all patients presenting between May 2012 and December 2022 with acute ocular surface burn (within 6 weeks from injury) with perilimbal scleral ischemia, without perforation or previous surgical intervention for the same. All these patients underwent single-stage tenonplasty with amniotic membrane transplantation and medical management. Successful outcome was defined as globe preservation at 6 months. Results: Twenty-three eyes of 20 patients were included in our study. Out of these, alkali was the most common offending agent (10 eyes of 8 patients). The extent of scleral ischemia was <90° in seven eyes, 90°–180° in six eyes, and >180° in 10 eyes. The mean interval between the injury and tenonplasty was 16.5 days. Globe integrity in 20 of the 23 eyes was maintained 6 months post injury. Three eyes that developed hypotony at the end of 6 months had more than 180° of perilimbal scleral ischemia at presentation. The extent of scleral ischemia correlated with the development of phthisis bulbi, but the values were not statistically significant (P = 0.081). Conclusion: Tenonplasty in the acute stage acts as a globe-salvaging procedure in acute chemical burns with perilimbal scleral ischemia. Extensive scleral ischemia in an acute chemical burn remains a poor prognostic factor for globe integrity in the long term.